2017
DOI: 10.2217/epi-2016-0132
|View full text |Cite
|
Sign up to set email alerts
|

SExual Epigenetic Dimorphism in The Human Placenta: Implications for Susceptibility During The Prenatal Period

Abstract: Aim: Sex-based differences in response to adverse prenatal environments and infant outcomes have been observed, yet the underlying mechanisms for this are unclear. The placental epigenome may be a driver of these differences. Methods: Placental DNA methylation was assessed at more than 480,000 CpG sites from male and female infants enrolled in the extremely low gestational age newborns cohort (ELGAN) and validated in a separate US-based cohort. The impact of gestational age on placental DNA methylation was fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 59 publications
6
79
1
1
Order By: Relevance
“…Since both clusters 2 and 3 are significantly younger than cluster 1 ( p < 0.01 and p = 0.02, respectively), this fits with the knowledge that placentas become progressively more methylated with time [ 36 ], while in cluster 3, a moderate bias in fetal sex ( p = 0.12) may have also been involved. Additionally, controlling for fetal sex and GA substantially increased the proportion of significant sites that showed a strong linear relationship with gene expression (5% to 9% in cluster 2; 2% to 8% in cluster 3), thereby confirming that a large number of sites in the genome undergo DNA methylation changes in response to differences in these two factors that are independent of epigenetic regulation and gene expression [ 9 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 98%
“…Since both clusters 2 and 3 are significantly younger than cluster 1 ( p < 0.01 and p = 0.02, respectively), this fits with the knowledge that placentas become progressively more methylated with time [ 36 ], while in cluster 3, a moderate bias in fetal sex ( p = 0.12) may have also been involved. Additionally, controlling for fetal sex and GA substantially increased the proportion of significant sites that showed a strong linear relationship with gene expression (5% to 9% in cluster 2; 2% to 8% in cluster 3), thereby confirming that a large number of sites in the genome undergo DNA methylation changes in response to differences in these two factors that are independent of epigenetic regulation and gene expression [ 9 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 98%
“…The most extensively profiled sexually dimorphic epigenetic mark is DNA methylation. Sex-specific methylation patterns have been observed in blood [74][75][76][77], placenta [78], liver [79][80][81][82], pancreas [83], muscle [84], heart [81], and brain [81,[85][86][87][88][89]. Sex differences in histone modifications have also been described, although thus far only in mouse brain [90,91].…”
Section: Sex Differences In Epigeneticsmentioning
confidence: 99%
“…Effects of prenatal exposure to endocrine disruptors & toxic metals on the fetal epigenome Review mental differences between placentas derived from male or female fetuses may result in sexually dimorphic responses to environmental exposures [132]. It has recently been shown that gene-specific methylation differs between male and female placentas and these genes are enriched for immune function, transport of substances across the placenta, and transcription factors [133]. Further substantiating these findings, femaleand male-derived placentas have differential expression levels of immune-related genes.…”
Section: Review Bommarito Martin and Frymentioning
confidence: 99%